Sociodemographic Comparison in Patients with Subjective and Objective Clinical Findings of Temporomandibular Dysfunctions - Sener, Sevgi; Akgunlu, Faruk (European Journal of Dentistry, 2011)
Objectives: To investigate the differences in healthy persons and patients with myofacial pain without limitation, objective signs of temporomandibular dysfunctions (TMDs), and both subjective and objective features with respect to age, gender, effects of TMDs on daily life, economic condition, smoking habit, marital status, and education. Methods: Sociodemographic information of 296 persons (212 females and 84 males) was evaluated. Subjects were categorized into 4 groups according to clinical findings: no TMD symptoms (control, C); myofacial pain without limitation (MP); objective signs (PWOS); or both subjective and objective features (MP/PWOS). Results: The C, MP, PWOS, and MP/PWOS groups comprised 64 (22%), 66 (22%), 68 (23%), and 98 (33%) subjects. PWOS and MP/PWOS differed significantly between the 15–30 and 30–45 year age groups. Although patients with PWOS were significantly higher in the 15–30 year age group, patients with MP/PWOS were significantly higher in the 30–45 year age group. A significant difference was observed with respect to gender in all groups except the control group. The effects of TMD symptoms on daily life differed statistically among the groups. Conclusions: Female gender is a risk factor for TMDs. Females are more vulnerable to subjective and objective signs than males. During general dental examinations, females should be checked for TMD symptoms. PWOS manifest before MP. Moreover, mechanical derangements can cause myofacial pain. MP can mostly affect daily life, but PWOS tend to be prohibitive. (Eur J Dent 2011;5:380-386)
Keywords: TMD; Age; Gender; Myofacial pain